Changes in body structure and renal function throughout life in patients with chronic diseases without renal insufficiency compared to healthy persons - Cieza Zevallos, Javier Antonio (2019)
Objective: To determine if there are differences between persons with chronic diseases with no renal insufficiency compared to health persons in body structure, renal function and dietary habits. Methods: Volunteer participants compared by age (20-80 years); body mass index (BMI 20-25 kg/m2) and serum creatinine <1.1 mg/dl were included. Study design, a comparison of independent groups, group 1 (n=50) healthy adults without known previous condition not taking any medication and with a satisfactory quality of life, group 2 (n=46) persons with any chronic condition of > 3 months. Weight, height, body water, body fat, lean body mass measured by electric bioimpedance; serum urea and creatinine and urine creatinine, electrolytes and urea were measured in both groups. Creatinine and urea clearance, daily protein intake and daily consumption of sodium salt and potassium were measured. SPSS v.18 was used to analyze data. Results: no difference in body structure between groups was found. A significant difference between groups (p<0.05) in ClCr (126.6 ± 42.3 and 96.2 ± 48.1 ml/min/1.73m2SC), ClUrea (57.0 ± 25.9 and 44.3 ± 30.7 ml/min/1.73m2SC), serum creatinine (0.74 ± 0.16 and 0.67 ± 0.17 mg/dl), daily urine creatinine /kg (20.5 ± 6.6 and 13.7 ± 6.1 mg/kg), daily protein intake (0.89 ± 0.38 and 0.64 ± 0.46 g/kg/d) and daily intake of potassium (0.89 ± 0.39 and 0.65 ± 0.39 mEq/kg/day). Conclusions: chronic diseases reduce early the renal function, urinary excretion of creatinine and reduce daily intake of proteins and potassium compared to healthy people. These abnormalities do occur despite of normal serum creatinine levels.